Analysis of the Effect of Capital Structure, Corporate Governance and Intellectual Capital on the Possibility of Financial Distressin Coal Mining Companiesin Indonesia and Australia - Mutia Fitri Chania; Khaira Amalia Fachrudin; Amlys Syahputra Silalahi (Budapest International Research and Critics University, 2022)
The purpose of this study is to analyze and find out how the influence of capital structure, corporate governance and intellectual capital on the possibility of companies experiencing financial distress in coal mining companies in Indonesia and Australia. The population of this study are coal mining companies listed on the Indonesia Stock Exchange and the Australian Stock Exchange for the 2016-2020 period. The research sample is 18 coal mining companies on the Indonesia Stock Exchange and 18 coal mining companies listed on the Australian Stock Exchange for the 2016-2020 period. The data analysis technique used logistic regression analysis with the SPSS program to test these variables. The evidence proves that (1) capital structure has a significant positive effect on the possibility of companies experiencing financial distress in Indonesian coal mining companies and Australian mining companies, (2) board size has a positive and insignificant effect on the possibility of companies experiencing financial distress in state coal mining companies. Indonesia and has a negative and insignificant effect on Australian mining companies, (3) board composition has a negative and insignificant effect on the possibility of companies experiencing financial distress in Indonesian state coal mining companies and has a positive and insignificant effect on Australian mining companies, (4) audit committee has a negative and insignificant effect on the possibility of the company experiencing financial distress at the Indonesian state coal mining company and a positive and significant effect on the company Australian mining companies, (5) remuneration committee has a positive and insignificant effect on the possibility of companies experiencing financial distress in Indonesian coal mining companies and negative and significant effects on Australian mining companies, (6) intellectual capital (VAIC) has a negative and insignificant effect on the possibility of the company experiencing financial distress in a coal mining company from Indonesia to the state of Australia